Hubungan Kesiapsiagaan Remaja Dengan Keterampilan Menghadapi Bencana Banjir di Desa Padas Kecamatan Tanon, Kabupaten Sragen - Rysta Aditiya Permadani; Tri Susilowati (Jurnal Keperawatan Duta Medika, 2022)
Background: The World Health Organization (WHO) conveys that a disaster in English is understood as a disaster is any event that causes damage, loss of human life. The territory of Indonesia is located in a tropical climate area with two seasons, namely the dry season and the rainy season. The National Disaster Management Agency (BNPB) recorded that 424 disaster events occurred in Indonesia in November 2019 and these events were domiciled by floods. Floods have also caused hundreds of houses to be submerged, thousands of hectares of agricultural area. From the data collected, there are 842 hectares of submerged agricultural area. The water level in the agricultural area reaches more than two meters, resulting in hundreds of hectares of land like a sea of ​​water. Objective: to analyze the relationship between adolescent preparedness and skills in dealing with floods in Padas Village, Tanon District, Sragen Regency. Methods: this study uses a quantitative method that is analytic survey. Sampling using purposive sampling technique with a total sample of 68 respondents. Analysis of the data used in this study in the form of bivariate analysis using the Chi-Square test. Results: the results of the Chi-Square test obtained a p-value of 0.002 < (0.05) so that there is a relationship between adolescent preparedness and skills in dealing with floods in Padas Village, Tanon District, Sragen Regency. Conclusion: There is a relationship between adolescent preparedness and skills facing flood disaster in Padas Village, Tanon District, Sragen Regency.